Uma abordagem para construção de mashups de dados especificados como uma visão sobre um EKG - Cruz, Matheus Mayron Lima da (2021)
Enterprise Knowledge Graphs (EKG) that apply Semantic Web technologies and linked data principles have become increasingly attractive solutions for companies and organizations. This attention is due to the ability of these EKGs to offer a unified and flexible layer over data sources. In this context, the semantic layer provided by an EKG can be used to support the process of building data mashups, which are materialized views built from the collection, transformation and combination of data from different sources . This work presents an approach for building data mashups as views over an EKG.